The Effect of Touch and Talk Therapy on Reducing Anxiety in Hospitality Children - Tri Peni; Tri Ratnaningsih; Siti Indatul Laili (Journal of Ners and Midwifery, 2023)
Hospitalization causes impacts on children such as the impact of separation, loss of control, and illness or pain. Children feel hopeless, protest, uncooperative, and depressed. Children who are sick and have to be hospitalized will have a difficult time because they cannot carry out their habits. The environment and unfamiliar people, care, and various procedures that children undergo are the main sources of stress, disappointment, and anxiety. If not treated immediately, the impact of hospitalization will affect psychosocial development, especially in children. The research aimed to determine the effect of touch and talk therapy on reducing anxiety in hospitalized children in the children's care room at RA Basoeni Regional Hospital, Mojokerto Regency. The design used Pre-Experimental with one Group Pre-Post Test approach. The population in this study were all children who were hospitalized in the children's care room at RA Basoeni Regional Hospital. The sampling technique used purposive sampling, obtaining a sample of 27 respondents. Data analysis used the Wilcoxon signed Ranks test. The instrument used the modified DASS-14 anxiety questionnaire. Touch and talk therapy influences the anxiety level of hospitalized children in the children's care room at RA Basoeni Regional Hospital, Mojokerto. Touch and talk therapy involves touching the child while providing motivation or telling stories to create a relaxed and comfortable condition. Children feel happy and there is a diversion of attention which makes them happy, thereby reducing anxiety in children undergoing hospitalization.